Pengembangan Kompetensi Profesional Guru Melalui Kebijakan Sertifikasi - Siswanto, Heru (MADINAH, 2018)
Certification of teacher have been accounted for as one of the education core reforms to improve teacher professionalism. The release of the Act No. 14/ 2006 for Teacher and Lecturer (at higher education) is noticeable to be a historical tombstone which sets teacher and lecturer as profession as well as doctor , engineer or others. This will change the public perception to teacher to become more positive, to build up the teacher self-confident, and to magnetize the interest of those first quality candidates to turn out to be teachers, and to give the public trust back to school as an educational institution. It is highly recommended that the enhancement of teacher professional capacity to be integrated with the instructional activities implemented at schools, which, on one hand are capable of improving their quality of teaching as teachers, on the other hand capable of giving them the opportunities to improve their professional capacity while toting-up their cummulative credits mandatory for teacher certification.